Improving resolution in two orthogonal orientations from a single-shot digital holographic microscopy - Krishnendu Samanta; Anupriya Tiwari; Samsheerali P.T.; Joby Joseph (Results in Optics, 2024)
We demonstrate a single-shot digital holographic microscopy technique to improve the diffraction-limited resolution in two orthogonal orientations simultaneously by dual-channel orthogonal polarization multiplexing approach. Orthogonally polarized two oblique beams are employed to illuminate the sample and two reference beams with mutually orthogonal polarization are interfered with the object beams in a custom-designed Mach–Zehnder configuration. This technique is potentially beneficial to encode high frequency sample information from two orthogonal directions simultaneously in a single recorded hologram where the high frequency spectra is synthesized by the selective spectral stitching. Thus, the resolution is enhanced along two orientations from a single-shot hologram in this work. Both the simulation and experimental results are shown for the proposed technique with around 2-fold resolution enhancement over the diffraction limit.